The dynamic case-based learning model: conducive to enhancing the practical learning effectiveness of dermatology for medical students - Li, Yidan; Lei, Li; Jiang, Ling; Mao, Ping; Fu, Chuhan; Chen, Jing; Zeng, Qinghai (BMC medical education, 2025)
In dermatological diseases, skin lesions are often subject to dynamic changes. However, under the traditional learning model, medical students lack a dynamic understanding of skin lesions and clinical diagnosis and treatment procedures. This study proposes the dynamic case-based learning (DCBL) model, which was presented through typical dynamic cases. We surveyed 129 undergraduate students and 53 clinical dermatologists to gain an understanding of perceptions of the DCBL model. Eighty percent of students felt very satisfied or satisfied with the DCBL model. They self-evaluated that the new model would greatly improve their attention (92.2%), learning interest (89.9%), self-directed learning ability (89.9%), dynamic understanding of lesions (96.9%), and ability to diagnose and treat skin diseases (95.4%). Additionally, a significant proportion of teachers also believed that students could improve across multiple dimensions, including self-directed learning ability (96.2%) and dynamic understanding of skin lesions (98.1%). Most clinical dermatologists and students participating in this study expressed a positive attitude towards the DCBL model. According to their perceived responses, the model appears to effectively stimulate the enthusiasm of students for learning, enhance their dynamic understanding of skin diseases, help them to train diagnostic and therapeutic thinking, and improve their diagnosis and treatment skills. However, further empirical research is required to directly assess its impact on the enhancement of diagnostic and treatment abilities in dermatology, as well as its overall effectiveness.